Produksi Enzim Inulinase Khamir Pichia manshurica DUCC Y-015 Dari Tepung Umbi Dahlia (Dahlia variabilis Willd.) Dengan Variasi Konsentrasi Magnesium Sulfat (MgSO4.7H2O) Dan Waktu Inkubasi - Riza Laksita Devi Mutiaratri; W Wijanarka; Sri pujiyanto (Jurnal Akademika Biologi, 2015)
Dahlia tubers (Dahlia variabilis Willd.) contain inulin which can be hydrolyzed by the inulinase enzyme (E.C.3.2.1.7) into fructose monomer units. Application of  inulinase enzyme is used in the production of HFS (High   Fructose  Syrup)  dan  FOS  (Fructo-oligosaccharides).  Inulinase  can  be  produced  by  several microorganisms  including  inulinolytic  yeast  Pichia  manshurica  DUCC  Y-015.  One  of  the  factors  that influence the production of enzyme inulinase is macro minerals and incubation time on production medium. This study aims to determine the concentration of magnesium sulphate (MgSO4.7H2O) and the most optimal incubation time in producing the inulinase  enzyme. The research was carried out experimentally using a Randomized Block Design factorial. The first factor is the concentration MgSO4.7H2O those are 0,5 g/L; 1 g/L; and 1,5 g/L. The second factor is the variation of the incubation time, those are 12 hours; 18 hours; and24 hours, repetition was performed three times. Data were analyzed using ANOVA with 5% significant level(α = 0,05) and Duncan Test for further analysis. The results showed that the variation of the concentration ofMgSO4.7H2O has not been able to increase the production of inulinase enzyme, while the incubation time of18 hours produced the inulinase enzyme activity of 0,9605 IU/mL. Keywords:  Inulinase,  Dahlia  variabilis  Willd.,  Pichia  manshurica  DUCC  Y-015,  MgSO4, Incubation Time